Implementation of Proxy Server in Internet Access Management - Angeria, Karisma; Mahfuzhi, A.R. Walad (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2025)
The advancement of network technology has made it easier to access information via the internet, but it also presents challenges in limiting access to websites that are irrelevant to academic activities, such as social media, adult content, and gambling. This study aims to implement an access control system using mikrotik devices with web proxy features to enhance network security and efficiency at the Faculty of Engineering, University of Muhammadiyah Bengkulu. The research method used is experimental, which involves directly observing the impact of web proxy configuration on internet access. The stages include problem identification, system design, implementation, and testing to evaluate the effectiveness of the applied system. Based on the test results, the system successfully blocked 26 non-academic websites categorized into 9 social media, streaming, and entertainment sites; 8 adult content sites; and 9 gambling sites. All websites on the list were effectively blocked, demonstrating the system’s success in creating a network environment more conducive to academic activities. Abstract -The advancement of network technology has made it easier to access information via the internet, but it also presents challenges in limiting access to websites that are irrelevant to academic activities, such as social media, adult content, and gambling. This study aims to implement an access control system using mikrotik devices with web proxy features to enhance network security and efficiency at the Faculty of Engineering, University of Muhammadiyah Bengkulu. The research method used is experimental, which involves directly observing the impact of web proxy configuration on internet access. The stages include problem identification, system design, implementation, and testing to evaluate the effectiveness of the applied system.Based on the test results, the system successfully blocked 26 non-academic websites categorized into 9 social media, streaming, and entertainment sites; 8 adult content sites; and 9 gambling sites. All websites on the list were effectively blocked, demonstrating the system’s success in creating a network environment more conducive to academic activities.